Falangist women at Franco’s Universities: The Sección Femenina of the Sindicato Español Universitario (1939-1965) - Barrera López, Begoña (Hispania Nova, 2021)
This paper analyses the Women’s Section of the Sindicato Español Universitario (Spanish University Union SEU) during Franco’s regime. Led by an elitist group of falangist women from the Sección Femenina (Women’s Section) of the FET-JONS, and under the male SEU as well, the activity of this group of SEU falangist women has been barely studied until now However, the Sección Femenina of the Sindicato Español Universitario (SF-SEU) was a space of power, sensitive both to the agitated life of Franco’s universities, to the development of a political falangist culture and, also, to the transformations of the Sección Femenina. Thus, it must be analysed in order to shed light on issues regarding gender and class identity promoted by Pilar Primo de Rivera’s organisation.